Improving the Teaching Process of Semiconductor Topics Based on an Innovative Approach (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article presents a method for improving the teaching process of semiconductor topics in the curriculum for the subject "Electricity and Magnetism" in higher education based on interactive methods.